2017
DOI: 10.11646/phytotaxa.302.1.5
|View full text |Cite
|
Sign up to set email alerts
|

A new araneogenous fungus in the genus Beauveria from Guizhou, China

Abstract: Beauveria araneola sp. nov., a fungus parasitic on spiders, was isolated from a spider at the Experimental Farm of the Institute of Entomology, Guizhou University, China; and described with morphological and phylogenetic evidences. This species differs morphologically from other species in the genus by its long slender denticulate rachis, cylindrical to ellipsoid conidiogenous cells, and ellipsoidal to globose conidia. Phylogenetic analyses based on three-locus (TEF, RPB1 and Bloc) data strongly support the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Sequence alignment and phylogenetic analyses DNA sequences generated in this study were assembled and edited using Lasergene 6.0 (DNASTAR, Madison, WI, USA). TEF, RPB1, and Bloc sequences from 19 taxa (18 Beauveria isolates and one Isaria cicadae strain as outgroup), and ITS sequences from 20 taxa (19 Beauveria isolates and one I. cicadae strain as outgroup) were downloaded from GenBank, based on Agrawal et al (2014), Ariyawansa et al (2015), Chen et al (2013), Chen et al (2017), Imoulan et al (2016), Robène-Soustrade et al (2016), Rehner & Buckley (2005), Rehner et al (2011), andZhang et al (2012). Multiple sequence alignments for TEF, RPB1 and Bloc were carried out using MAFFT v7.037b (Katoh et al 2013).…”
Section: Specimen Collection and Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence alignment and phylogenetic analyses DNA sequences generated in this study were assembled and edited using Lasergene 6.0 (DNASTAR, Madison, WI, USA). TEF, RPB1, and Bloc sequences from 19 taxa (18 Beauveria isolates and one Isaria cicadae strain as outgroup), and ITS sequences from 20 taxa (19 Beauveria isolates and one I. cicadae strain as outgroup) were downloaded from GenBank, based on Agrawal et al (2014), Ariyawansa et al (2015), Chen et al (2013), Chen et al (2017), Imoulan et al (2016), Robène-Soustrade et al (2016), Rehner & Buckley (2005), Rehner et al (2011), andZhang et al (2012). Multiple sequence alignments for TEF, RPB1 and Bloc were carried out using MAFFT v7.037b (Katoh et al 2013).…”
Section: Specimen Collection and Isolationmentioning
confidence: 99%
“…The host taxa in which pathogenic Beauveria have been found include Araneae, Blattariae, Coleoptera, Diptera, Embioptera, Heteroptera, Homoptera, Hymenoptera, Isoptera, Lepidoptera, Mantodea, Neuroptera, Orthoptera, Siphonaptera, and Thysanoptera (Zimmermann 2007, Chen et al 2017 Recently, entomopathogenic fungi were screened in Guizhou, China, and we isolated a grub-infecting Beauveria strain. Based on morphological characteristics and phylogenetic analysis, we concluded that this strain represents a new species and is described herein as B. majiangensis.…”
Section: Introductionmentioning
confidence: 99%
“…Both taxa were complexes of species consisting of morphologically similar but cryptic lineages. Following the novel molecular approach in Beauveria taxonomy, several new species have been described [55,[68][69][70][71][72][73][74]. Up until now, five species (B. bassiana, B. brongniartii, B. caledonica, B. pseudobassiana, and B. varroae S.A. Rehner and Humber) have been documented in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Some new Cordyceps species were reported later from China (Li et al 2008, Liang et al 2008, Yang et al 2009, Cao et al 2010, Chen et al 2013b, Wen et al 2013, Yan & Bau 2014, Yang et al 2015, Zhou et al 2015, Yu et al 2017, Qu et al 2018a, 2018b, Wang et al 2018, Zha et al 2019. Furthermore, some anamorphic species of Cordyceps were also reported (Huang et al 2007, Zou et al 2010, Zhang et al 2013, Chen et al 2013a, 2017a, 2017b.…”
Section: Introductionmentioning
confidence: 99%